2018
DOI: 10.1177/2050312118818304
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of surgical patients with perioperative nursing care in a Spanish tertiary care hospital

Abstract: Objective:Although numerous studies have assessed patient satisfaction in diverse settings, in the realm of nursing surgical care, standardization of measurement for patient experience and satisfaction is lacking. Therefore, the aim of this study was to assess the satisfaction of surgical patients with perioperative nursing care.Method:A descriptive cross-sectional survey was conducted. Sociodemographic characteristics and clinical data were recorded. Patient satisfaction was measured with a modified version o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
10
1
2
Order By: Relevance
“…The level of patient satisfaction (60.5%) in our study was higher than the results obtained in other areas either in China or elsewhere, such as in Taiwan (35%) 39 Malaysia 22 and 11 western provinces in China (60%) 40 ; however, it was lower than that in Shandong, 41 Jiangxi 42 and other cities in Gansu, China, 33 43 and also in Spain 44 and Australia. 45 This might have been related to differences in sample size, region and the use of a different survey scale.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The level of patient satisfaction (60.5%) in our study was higher than the results obtained in other areas either in China or elsewhere, such as in Taiwan (35%) 39 Malaysia 22 and 11 western provinces in China (60%) 40 ; however, it was lower than that in Shandong, 41 Jiangxi 42 and other cities in Gansu, China, 33 43 and also in Spain 44 and Australia. 45 This might have been related to differences in sample size, region and the use of a different survey scale.…”
Section: Discussioncontrasting
confidence: 77%
“…62 Study has shown that patients who were well informed and understood the process had a better surgical experience. 44 However, this might have not been well revealed in our study as patients with surgery showed less satisfaction with nursing services. It is suggested that patients need to be assessed regularly for anxiety during the preoperative visit and appropriate anxiety-reducing methods should be introduced.…”
Section: Patients' Characteristicsmentioning
confidence: 60%
“…Nurses also provide education for the patient and the patient’s family and put in place plans for the patient’s homecare following discharge. It has been reported that surgical nurses have an important impact on patient satisfaction in the peri-operative period (Sillero Sillero & Zabalegui, 2018). Myles, Williams, Hendratam, Anderson, and Weeks (2000) reported that patient care was important in the postoperative period and patients’ satisfaction levels were high.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is an environment that requires specific training, and this becomes a way to provide the highest quality of care, as well as being an essential element in the identification and prevention of errors [10]. Specialized training in surgical areas ensures patient safety and is the cornerstone of clinical practice [11]. A clear description and identification of nursing competencies in the surgical field would make it easier for nurses working in these areas to be specialists with a formally acquired education [6].…”
Section: Introductionmentioning
confidence: 99%